(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The shocks that can damage detention facilities are numerous and of varying severity. However, an antifragile penitentiary system may be able to gain from disorder or, in other words, it can thrive even in the most difficult situations. In order to try achieving this goal, it is useful adopting a preventive approach, based on the recommendations contained in international soft law, integrated from the theories, introduced by Sendhil Mullainathan and Eldar Shafir as well as Nassim Nicholas Taleb, concerning the organizations and the complex systems.